Growth, Spectral, Optical, Thermal, Mechanical and Dielectric properties of CdCl2 added (Na)2 SbF5 Single Crystals (Journal of Pharmaceutical Negative Results, 2023)
Single crystals of pure and Cdcl2 added sodium penta fluro antimonates, an electro optical crystal has been grown by slow evaporation technique. The grown crystals are subjected to single crystal X-ray diffraction, Fourier Transform Infrared(FTIR) studies, EDAX,UV-Vis studies    and microhardness studies. Single crystal X-ray diffraction confirms that the crystal belongs to Orthorhombic  system. The FTIR  spectrum analysis has confirmed the functional groups in the grown crystal. The  optical  behaviour was examined by  UV-Vis studies and found that the crystal  is transparent in the entire visible region. Microhardness studies  reveals the mechanical strength of the grown Crystal. The decomposition point of  the sample was identified by TG/DTA studies.  The samples   was measured    and   Dielectric properties were  measured at different frequencies   and temperature.